2010
DOI: 10.1093/toxsci/kfq243
|View full text |Cite
|
Sign up to set email alerts
|

Small Amounts of Zinc from Zinc Oxide Particles in Sunscreens Applied Outdoors Are Absorbed through Human Skin

Abstract: Metal oxide nanoparticles are commonly used in personal-care formulations as protective agents against exposure to ultraviolet radiation. Although previous research has concluded that nanoparticles do not penetrate healthy skin, it remains contentious whether this conclusion holds under normal conditions of sunscreen use. Humans (n = 20) were exposed to sunscreens containing zinc oxide (ZnO) particles to determine if Zn from the particles was absorbed through skin over five consecutive days under outdoor condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
245
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(260 citation statements)
references
References 31 publications
11
245
0
4
Order By: Relevance
“…[16][17][18] To distinguish Zn in ZnO particles from the body's own Zn, 68 Zn was used to prepare ZnO particles. 19 Two types of particles were used, 19 nm NPs and .100 nm micro-sized particles. After application of sunscreen containing one of these two types of particles on the skin of healthy human volunteers for 5 days, approximately 0.1% of all Zn in the blood was 68 Zn.…”
Section: In Vivo Studies Effects Of Airway Exposure In Experimental Amentioning
confidence: 99%
“…[16][17][18] To distinguish Zn in ZnO particles from the body's own Zn, 68 Zn was used to prepare ZnO particles. 19 Two types of particles were used, 19 nm NPs and .100 nm micro-sized particles. After application of sunscreen containing one of these two types of particles on the skin of healthy human volunteers for 5 days, approximately 0.1% of all Zn in the blood was 68 Zn.…”
Section: In Vivo Studies Effects Of Airway Exposure In Experimental Amentioning
confidence: 99%
“…From the studies regarding skin exposure to nanoparticles [7,16,109,[117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133] several likely determinants of hazard emerge. These include size, chemical composition, surface characteristics, such as surface coating and surface charge, and crystalline structure.…”
Section: Human Health Hazards Following From Dermal Exposure To Persimentioning
confidence: 99%
“…Recent studies have demonstrated that small amounts of zinc from ZnO particles in sunscreens applied outdoors are absorbed through human skin. 1 In spite of these concerns, few studies have investigated the effects of ZnO NPs on the internal organs when they were applied to the skin repeatedly.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have proposed that there would not be any toxicologic concerns with dermally applied ZnO NPs; 11,12 however, others have demonstrated absorption of ZnO particles through human skin or in a model equivalent to human skin. 1,13 Hence, concerns about ZnO NPs are ongoing, not only with regard to possible skin toxicity, but also systemic toxicity. When ZnO NPs were administered through the oral or inhalational route, damage to the liver was evident.…”
mentioning
confidence: 99%
See 1 more Smart Citation